INFLUÊNCIA DA CAPTAÇÃO PLUVIAL EM TELHADOS NA DRENAGEM URBANA - Enio Arriero Shinma (2023)
This study aimed to assess the effects of rooftop rainwater harvesting storage volumes, focused on conserving potable water, as a strategy for attenuating surface runoff and mitigating drainage issues in urban areas. This investigative necessity emerged in light of the evident growth of urban infrastructure, which over the years has prioritized the adoption of impermeable pavements and the expansion of macrodrainage capacity. This scenario has resulted in heightened peak flows and escalated volumes of surface runoff. As a consequence of these interventions, urban areas have incurred various damages associated with the impacts of floods. Coupled with drainage-related implications, urban areas also face complexities in sustaining water supply, including challenges related to quantity, quality, and the distance between capture and consumption sites. Thus, it is incongruous to observe an excess of rainwater runoff causing damage, while simultaneously experiencing a scarcity of water to meet the population's needs. Accordingly, it is reasonable to conclude that both these problems could be alleviated through the adoption of rainwater harvesting and storage systems. Studies addressing rooftop rainwater harvesting often operate on a micro scale, detailing flow attenuation effects in buildings or small areas. Following their primary conclusions, they often suggest reducing the final discharge of urban macro drainage systems. This inference stems from the decrease in runoff volume in the analyzed property unit, disregarding well-known hydrological effects such as peak flow attenuation and volume reduction, as well as synchronization or desynchronization effects along the macro drainage network. Therefore, there is a gap to be filled through studies on the assessment of the effects of rooftop rainwater harvesting, both in terms of potable water savings and surface runoff in urban watersheds. Given this context, this thesis scrutinizes the effects of rooftop rainwater harvesting in attenuating macrodrainage runoff, considering the necessary storage volumes for potable water conservation. In the first chapter of this work, the potentials for potable water conservation were compared using two methodologies for quantifying roof areas, one statistical and the other employing artificial intelligence. In the second chapter, the effect of spatial discretization on the potential for potable water conservation was analyzed. The third chapter elucidated correlations between harvesting, consumption, population, and roof areas, for the measurement of necessary storage volumes to attain such potential. Following these analyses, in chapter four, hydrological-hydraulic modeling was used to determine the limits of influence of rooftop rainwater harvesting, in terms of potable water consumption equivalence, on peak flow and volume attenuation in urban macro drainage. Lastly, in chapter five, the influence of the volumes required to achieve the potential potable water savings through rooftop rainwater harvesting was analyzed as an alternative for attenuating surface runoff in urban macro drainage.